Pengaruh Kompetensi dan Skeptisisme Profesional terhadap Kemampuan Auditor Mendeteksi Kecurangan pada Kantor Akuntan Publik (KAP) Kota Medan - Fahmi, Muhammad; Syahputra, Sendi; Harahap, Riva Ubar (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2025)
This study analyzes the influence of competence and professional skepticism on auditors' ability to detect fraud in Public Accounting Firms (KAP) in Medan. Data were collected via questionnaires and analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) 4.1. The results indicate that competence has a positive and significant effect on auditors' fraud detection ability (coefficient 0.371, t-statistic 3.334, p-value 0.001). Professional skepticism also has a significant effect (coefficient 0.574, t-statistic 5.085, p-value 0.000). Outer Loading values above 0.7 confirm the validity of the measurement model. These findings align with previous research, indicating that auditors with high competence and skepticism are more effective in detecting fraud. This study suggests that Public Accounting Firms should enhance auditor training and professionalism to improve fraud detection effectiveness.